2013
DOI: 10.4081/aiua.2013.3.130
|View full text |Cite
|
Sign up to set email alerts
|

Erectile function after repeat saturation prostate biopsy: Our experience in 100 patients

Abstract: Repeat transperineal SPBx under sedation did not significantly worsened erectile function; the minimal risk of temporary post-biopsy ED could be previously discussed (not emphasised) with potent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…So far is not clearly defined by the international literature whether serial PNBx predispose to a permanent ED over time: nevertheless only few studies, as the one leaded by Hilton et al, showed a total absence of correlation between this side effect and the procedure (14). In the majority of the examined studies, the investigators demonstrated a short-term (30 days) impact on EF, asso- ciated to psychological factors as anxiety and diagnosis of PCa (8,10) rather than to use of periprostatic nerve block and flogosis linked to the procedure. Some authors considered PNBx follow-up at 1 and 6 months: Akbal et al showed a worsened EF 1 month after PNBx that returns at baseline level at 6 months (3): in this study the authors analyzed specifically only PCa-free patients, avoiding bias due to the cancer detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far is not clearly defined by the international literature whether serial PNBx predispose to a permanent ED over time: nevertheless only few studies, as the one leaded by Hilton et al, showed a total absence of correlation between this side effect and the procedure (14). In the majority of the examined studies, the investigators demonstrated a short-term (30 days) impact on EF, asso- ciated to psychological factors as anxiety and diagnosis of PCa (8,10) rather than to use of periprostatic nerve block and flogosis linked to the procedure. Some authors considered PNBx follow-up at 1 and 6 months: Akbal et al showed a worsened EF 1 month after PNBx that returns at baseline level at 6 months (3): in this study the authors analyzed specifically only PCa-free patients, avoiding bias due to the cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this well-documented side-effects, an increasing number of articles is showing a possible role of PNBx to cause Erectile Dysfunction (ED) (4)(5)(6). Some studies described this effect as temporary (7)(8)(9), and attributed to anxiety (9) rather than a real organic injury (6). Moreover, this studies often investigated Erectile Function (EF) in patients on active surveillance, that is to say with a diagnosis of prostate cancer, a potential negative psychological confounder that may influence their EF (10).…”
Section: Introductionmentioning
confidence: 99%
“…Pepe et al reported on erectile function in 100 men who underwent repeated TPSBx, and concluded that serial TPSBx did not significantly worsen erectile function in the short to medium-term [ 9 ]. In contrast, our data suggests that serial TPSBx increases the risk of ED at one, three, and six months postbiopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term complications of TPSBx typically include haematuria, acute urinary retention, and dysuria [ 5 , 8 ]. There have been relatively few reports on ED after serial sector biopsies performed via the transperineal route [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Others have not corroborated this observation. 8,9 In conducting this survey, we felt it important to define the needed test characteristics for an alternative to serial TRUS-BX among men on AS, as the scientific biomarker and imaging breakthroughs continue to emerge and improve. When we began this study, we expected that a particular value of false-negativity (i.e., the chance of missing a significant cancer via a biopsy alternate) would emerge to guide patients, physicians, and biomarker companies.…”
Section: Discussionmentioning
confidence: 99%